The Final Frontier of Logistics: Artificial Intelligence in the Last Mile Delivery - Natesh Kumar, Nitin (International Journal of Supply Chain Management, 2025)
Last-mile delivery (LMD), the most critical segment of the modern supply chain (SC), plays a vital role in shaping customer satisfaction but also accounts for the highest cost among all supply chain activities. Particularly in the context of e-commerce, it serves as a key differentiator while grappling with challenges such as rising customer expectations, urban traffic congestion, adverse weather, and sustainability concerns. This article explores how Artificial Intelligence (AI) and its subset, Machine Learning (ML), can be leveraged to optimize last-mile delivery. With the growing wave of digital transformation across the globe, this area is gaining increased attention. The article adds to the relatively limited body of research on this topic and concludes that AI and ML have the potential to significantly enhance supply chain efficiency, especially in last-mile delivery, by reducing costs, accelerating delivery speeds, and ultimately improving customer satisfaction.